Urgency of the Contempt of Court Criminalization Policy to Overcome Harassment Against the Status and Dignity of Courts - Disemadi, Hari Sutra; Roisah, Kholis (Faculty of Law, Universitas Brawijaya, 2019)
In Indonesia, many cases that occur related to contempt of court and law enforcement have occurred. The issue of Contempt of Court in Indonesia is a problem that is both interesting and complicated in its conception and regulation. Until now, in Indonesia, no provisions specifically regulating the Contempt of Court institutions. This completed study uses a normative juridical research method that prioritizes secondary data. This research addressing the legislation governing the Contempt of Court specifically until now still does not yet exist. However, the general arrangement has happened in the Criminal Code. Contempt of Court can occur both in the courtroom and outside the trial both in criminal, civil and industrial relations cases. Increasingly expanding various actions, which can be categorizing as contempt of court in Indonesia, it is necessary to arrange Contempt of Court in the form of separate rules